The oxford handbook of lived Buddhism - Bruntz, Courtney; Schedneck, Brooke (Oxford handbooks series, 2025)
Examines diverse ways that Buddhism is expressed and experienced in the everyday lives of lay people and monastics by particular people, through concrete practices, in certain places, within specific cultural and historical contexts